Defining aspects of adult motivation for learning in the context of lifelong learning - Cotruța, Dionisie (CEP USM, 2024)
Motivation has been considered from the perspective of psychodynamic orientation as a stimulation and discharge of energy; associated from the behaviourist approach to a stimulus, as a learned reaction; seen as a psychological factor influencing behaviour. Motivation as an influencing factor in lifelong learning tendencies and as a landmark in the lifelong learning process is gaining momentum in today’s society, becoming increasingly common among both researchers and educational institutions. While the education of school pupils has long been the main focus of educational institutions, the importance of adult education is now becoming increasingly apparent. It is widely recognized that adult education plays a crucial role in promoting a prosperous society. Consequently, the relevance of adult education and the factors that motivate adults to learn are increasingly important.

Motivația a fost considerată din perspectiva orientării psihodinamice ca o stimulare și descărcare de energie; asociată prin prisma abordării behavioriste unui stimul, ca o reacție învățată; văzută ca un factor psihologic ce influențează comportamentul. Motivația ca factor de influență în tendințele învățării pe tot parcursul vieții fiind un punct de reper în procesul de formare continuă capătă amploare în societatea actuală, devenind tot mai des întâlnit în rândul atât a cercetătorilor cât și a instituțiilor de învățământ. În timp ce educația elevilor a fost mult timp obiectivul principal al instituțiilor de învățământ, importanța educației adulților devine acum tot mai evidentă. Este larg recunoscut faptul că educația adulților joacă un rol crucial în promovarea unei societăți prospere. În consecință, relevanța educației adulților și factorii care îi motivează pe adulți să învețe sunt tot mai importante.
Aspecte definitorii ale motivației adulților pentru învățare în contextul învățării pe tot parcursul vieții
Keywords: motivation; adult motivation; adult motivation for learning; learning; motivație; motivația adultului; motivația adulților pentru învățare; învățare